Comment on ?Algal mediated intervention for the retrieval of emerging pollutants from aqueous media? - Chu K.H.; Hashim M.A.; Hayder G. (Elsevier B.V., 2025)
Addressing inaccuracies in review articles is essential to prevent the proliferation of misinformation. This communication is dedicated to rectifying factual errors identified in a recent review article featured in this journal, with a specific emphasis on addressing errors related to the Temkin, Flory?Huggins, Sips, and Baudu isotherm models. By elucidating and clarifying these inaccuracies, we aim to uphold the integrity of scientific discourse and ensure the accurate dissemination of information within the scholarly community. ? 2024 Elsevier B.V.